Biodegradation of polybutylene adipate-co-terephthalate by Priestia megaterium, Pseudomonas mendocina, and Pseudomonas pseudoalcaligenes following incubation in the soil. (November 2022) - Wei, Shiwei; Zhao, Yujin; Zhou, Ruimin; Lin, Jingwei; Su, Tingting; Tong, Haibin; Wang, Zhanyong
Abstract: Soil that contained polybutylene adipate-co-terephthalate (PBAT) was incubated with Priestia megaterium, Pseudomonas mendocina, and Pseudomonas pseudoalcaligenes to improve the biodegradative process of this polymer. The mixture of Pr. megaterium and Ps. mendocina was highly effective at biodegrading the PBAT, and after eight weeks of soil incubation, approximately 84% of the PBAT film weight was lost. Mixtures of the other two species also positively affected the synergistic degradation of PBAT film in the soil, but the mixture of three species had a negative effect. The residual PBAT film microstructure clearly demonstrated the degradation of PBAT, and the degree of degradation was related to the different species. Cleavage of the PBAT film ester bond after soil microbial action affected its properties. The incubation of PBAT in soil that contained these species affected soil dehydrogenase and soil lipase in particular. The secretion of lipase by these species could play an important role in the degradation of PBAT in the soil. Graphical abstract: Image 1 Highlights: Three Strains were applied to degrade PBAT films in soil. Mixture of Pr. megaterium and Ps. mendocina showed an excellent biodegradability. Three-strain mixture had a negative effect on PBAT biodegradation. Soil lipase plays an important role in the degradation of PBAT.